DETECTION OF SARS-COV-2 USING SALIVA - Rahatina, Vilianti Eka Fitri; Adi, Mateus Sakundarno (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
Background: Since December 2019, a new and infectious type of pneumonia has been detected early in Wuhan, Hubei, and then spread rapidly throughout the world. By March 11th, 2020, WHO finally declared the infectious disease a pandemic. Research on the use of saliva as a method of detecting SARS-Cov-2 has been carried out throughout the world. However, to the best of our knowledge, not many literature reviews have reported on the use of saliva as a sample for the diagnosis of Covid-19. Method: This study aims to report interactively on the use of saliva as a sample for the diagnosis of Covid-19.Result: There are 9 articles that meet research criteria, namely: using a cohort and cross-sectional study design, not a review, case report, letters of editor or protocol, research using saliva as a detection tool, articles published from January to December 2020. Most saliva samples were compared with Nasopharyngeal swab sample for Covid-19 detection. Viral nucleic acids found in saliva obtained from the ducts of the salivary glands may indicate the presence of infection in these glands. Live virus can be detected in saliva through viral culture.Conclusion: Saliva samples show great potential in the detection of Covid-19 and can be recommended as an alternative to simple and non-invasive tests.